The Effect Of Job Satisfaction On Employee Engagement Through Organizational Commitment On Employees Of PT Pabrik Gula Candi Baru Sidoarjo - Addis Pratama; Khoirur Rozaq (Universitas Negeri Surabaya, 2025)
This study aims to analyze the effect of job satisfaction on employee engagement through organizational commitment among employees of PG Candi Baru Sidoarjo. A quantitative approach was employed to examine the relationships among the variables. The population consisted of all employees of PG Candi Baru Sidoarjo, with 105 respondents selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using the Structural Equation Model Partial Least Square (SEM-PLS) with SmartPLS 3.0. The results show that job satisfaction has a positive and significant effect on employee engagement and organizational commitment. In addition, organizational commitment also has a positive effect on employee engagement. The mediation analysis indicates that organizational commitment is able to mediate the relationship between job satisfaction and employee engagement. These findings suggest that higher job satisfaction can strengthen organizational commitment, which in turn enhances employee engagement. Therefore, organizations are encouraged to improve job satisfaction and strengthen organizational commitment as strategic efforts to achieve more optimal and sustainable employee engagement.